2014
DOI: 10.1002/term.1942
|View full text |Cite
|
Sign up to set email alerts
|

Bone mechanobiology, gravity and tissue engineering: effects and insights

Abstract: Bone homeostasis strongly depends on fine tuned mechanosensitive regulation signals from environmental forces into biochemical responses. Similar to the ageing process, during spaceflights an altered mechanotransduction occurs as a result of the effects of bone unloading, eventually leading to loss of functional tissue. Although spaceflights represent the best environment to investigate near-zero gravity effects, there are major limitations for setting up experimental analysis. A more feasible approach to anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 166 publications
1
14
0
Order By: Relevance
“…Since years, investigators take advantage of microgravity simulation techniques that can be performed on Earth; several studies have been carried out in vitro by means of cell bioreactors and tissue engineering approaches (Pardo et al, 2005;Ko et al, 2010). A microgravity environment can be simulated on Earth through several in vivo systems, such as in the case of bed-rest tests for human volunteers (Ruggiu and Cancedda 2014;LeBlanc et al, 1987;Noble 2003;Zerwekh et al, 1998;Ziambaras et al, 2005), or hind limb unloading (HLU) test for rodents (Saxena et al, 2011;Visigalli et al, 2010). Particularly, a limited number of publications revealed that short-term mice exposition to simulated microgravity (HLU) produced a bone volume density loss similar to that observed by our long-term experimentation.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…Since years, investigators take advantage of microgravity simulation techniques that can be performed on Earth; several studies have been carried out in vitro by means of cell bioreactors and tissue engineering approaches (Pardo et al, 2005;Ko et al, 2010). A microgravity environment can be simulated on Earth through several in vivo systems, such as in the case of bed-rest tests for human volunteers (Ruggiu and Cancedda 2014;LeBlanc et al, 1987;Noble 2003;Zerwekh et al, 1998;Ziambaras et al, 2005), or hind limb unloading (HLU) test for rodents (Saxena et al, 2011;Visigalli et al, 2010). Particularly, a limited number of publications revealed that short-term mice exposition to simulated microgravity (HLU) produced a bone volume density loss similar to that observed by our long-term experimentation.…”
Section: Introductionsupporting
confidence: 75%
“…However "microgravity" is commonly used as a synonym for "unloading condition" and this paper followed this convention (Ruggiu and Cancedda 2014). Since years, investigators take advantage of microgravity simulation techniques that can be performed on Earth; several studies have been carried out in vitro by means of cell bioreactors and tissue engineering approaches (Pardo et al, 2005;Ko et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Throughout life, the bones are constantly remodeled by means of two coordinated and synchronized processes, including osteoblast-driven bone formation and osteoclast-driven bone resorption. This remodeling helps the bones adapt to changing loads with the optimized morphological structure and is therefore sensitive to mechanical stimulation alterations [1]. Skeletal unloading can disrupt the physiological process of bone remodeling and can induce severe bone loss, especially in weight-bearing bones.…”
Section: Introductionmentioning
confidence: 99%
“…Microgravity during space flight leads to decreases in the mineral content of bone, bone matrix protein production and bone formation, resulting in bone loss and osteoporosis [ 13 , 14 ]. A clinostat can be used to provide valuable information about mechanotransduction as it relates to bone homeostasis in bone cells, as well as for in vitro mechanobiology studies in the bone microenvironment [ 14 , 15 ]. Maintenance of bone homeostasis is based on the regulation of biochemical responses through balancing the activities of osteoblasts, osteoclasts, and osteocytes based on mechanosensitive signal transduction from microenvironmental forces, including mechanostimulation and mechanical stress.…”
Section: Introductionmentioning
confidence: 99%